Experimental investigation of the characteristic of vacuum spray cooling for tofu - Li, Gailian; Han, Lucong; Du, Shuaihua; Peng, Yuhang; Zhang, Zhenya; Cheng, Chuanxiao; Jin, Tingxiang (Frontiers in Food Science and Technology, 2023)
The present study proposes a rapid cooling method based on vacuum spray cooling, and establishes an experimental system to study the cooling performance of this method by taking tofu as an example. In this study, the effects of vacuum spray cooling, vacuum cooling and immersion vacuum cooling on the cooling rate, water holding rate, PH, TPA and other properties of tofu were compared. The total cooling time of vacuum spray cooling (13.86 min) was shorter than that of immersion vacuum cooling (33.39 min) but longer than that of vacuum cooling (10.64 min) for a temperature decrease from 70°C to 4°C. For weight loss from 70°C to 4°C, vacuum spray cooling (2.96%) was significantly less than that of vacuum cooling (10.21%). The PH value after cooling has no significant difference, but the color difference and water holding capacity of the sample after vacuum spray cooling are obviously better. However, the textural properties of the sample cooled by vacuum spray cooling were close to (for elasticity and viscosity) and better (for hardness and chewiness) than those of immersion vacuum cooling. In addition, compared with the two cooling methods in terms of storage, vacuum spray cooling can effectively maintain the moisture content, water holding rate, PH, chromatism and TPA of tofu, thus extending the fresh-keeping period of tofu. The conclusions of this paper provide theoretical support for prolonging the preservation period of food and optimizing the cooling process.